ANALISIS KEABSAHAN PERJANJIAN JUAL BELI MELALUI MEDIA ELEKTRONIK DENGAN PEMBAYARAN PAYLATER (BAYAR NANTI) MENURUT KUH PERDATA - Akmal Taufiq Ridho; Rangga Aditya Rastra Pradana (JOURNAL SAINS STUDENT RESEARCH, 2023)
The use of e-commerce media in the world of trade will have an impact on the international world in general and Indonesian society in particular. This relates to very important legal issues. The importance of selling agreements via electronic media and knowing the legal protection for sellers and buyers if one party defaults. This research aims to analyze the validity of sales and purchase agreements via electronic media with PayLater (Pay Later) payments according to the Civil Code. The approach used is normative juridical with the method used is research with reference to law including literature study. The objects used in this research are Law Number 8 of 1999 concerning Consumer Protection, the Civil Code, aspects of contracts and other relevant instruments. The results of this research indicate that the sale and purchase agreement via electronic media with PayLater (Pay Later) payment has legal validity in accordance with the Civil Code. Both parties must fulfill the conditions specified in the agreement, namely mutual recognition and understanding of the rights and obligations agreed upon by the parties. Apart from that, the party who is obliged to pay must also submit or obey the provisions regarding debt obligations so that the agreement can be maintained. Therefore, legal personnel must be careful in helping their clients to follow legal regulations so as not to cause legal problems.